2005
DOI: 10.1111/j.1365-294x.2005.02653.x
|View full text |Cite
|
Sign up to set email alerts
|

Clonal and spatial genetic structures of aspen (Populus tremuloides Michx.)

Abstract: To portray aspen clonal and spatial genetic structures, we mapped and genotyped trees in two 1-ha plots, each containing three aspen cohorts originating from fire or subsequent secondary disturbances. We used four microsatellite loci to identify aspen clones and increment core analysis to determine tree age. Clonal dimensions were measured by the maximum distance between two ramets and the number of ramets per genet. Standard normal deviate (SND) was used to assess the spatial distribution of aspen genets and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
40
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 43 publications
8
40
0
Order By: Relevance
“…In our study, the mean H O and H E were 0.476 and 0.591, respectively. Similar values were also reported in other related species, such as P. tremuloides (H O = 0.472, H E = 0.67; Namroud et al, 2005) and Populus tremula (H O = 0.474, H E = 0.500; Lexer et al, 2005).…”
Section: Genetic Diversitysupporting
confidence: 87%
“…In our study, the mean H O and H E were 0.476 and 0.591, respectively. Similar values were also reported in other related species, such as P. tremuloides (H O = 0.472, H E = 0.67; Namroud et al, 2005) and Populus tremula (H O = 0.474, H E = 0.500; Lexer et al, 2005).…”
Section: Genetic Diversitysupporting
confidence: 87%
“…Based on dominance index, we inferred that the ramets of both sexes presented a rather clumped occurrence within a genet, a pattern defined as the phalanx strategy of growth, commonly found in many woody species (Peterson and Jones 1997) including species from Populus (Namroud et al 2005;Chenault et al 2011;Cristobal et al 2014). Spatial analysis also detected the non-random distribution of individuals (ramets) of both sexes in space (Table 2).…”
Section: Sex-specific Clonal Architecture and Growthmentioning
confidence: 86%
“…DNA amplification was performed using Taq polymerase (Gibco from Invitrogen TM Life Technologies, Burlington, Canada) and four dyelabeled oligonucleotide primers (PTR1, PTR2, PTR3, and PTR4) at microsatellite loci complementary to Simple Sequence Repeat (SSR) flanking regions. The resolving power of these four microsatellites was tested in a previous study (Namroud et al, 2005b) and was found to be sufficiently high to reject the null hypothesis of similar genotypes (P (ID) <0.001).…”
Section: Dna Extraction and Amplificationmentioning
confidence: 99%